Expanding Horizon: The Role of Reconfigurable Intelligent Surfaces in Enabling Massive Connectivity - Adasme-Soto, P; Ayub-, M (Institute of Electrical and Electronics Engineers Inc., 2024)
This comprehensive article explores the integration of reconfigurable intelligent surfaces (RIS) with massive multiple input and multiple output (mMIMO) systems for future wireless networks, focusing on millimeter-wave (mmWave), beyond 5G (B5G), and sixth-generation (6G) technologies. It provides an in-depth understanding of the theoretical foundations of RIS and mMIMO, discussing their advantages, limitations, and unique capabilities in achieving massive connectivity. This article also highlights role of RIS in enhancing the performance of various wireless systems, including IoT, 5G, B5G, and 6G communications. The paper concludes by identifying open challenges and opportunities in RIS for massive connectivity, offering a roadmap for future research in this rapidly evolving field. © 2024 IEEE.